2019
DOI: 10.3389/fonc.2019.00404
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Patterns of Disparities in Burden of Lung Cancer in the United States, 1974-2015

Abstract: Background: Although lung cancer incidence and mortality have been declining since the 1990s, the extent to which such progress has been made is unequal across population segments. Updated epidemiologic data on trends and patterns of disparities are lacking. Methods: Data on lung cancer cases and deaths during 1974 to 2015 were extracted from the Surveillance, Epidemiology, and End Results program. Age-standardized lung cancer incidence and mortality and their annual percent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 41 publications
5
26
0
Order By: Relevance
“…As regards the impact of cervical cancer patients clinical features on pathological types of lung cancer, our study highlight that the incidence of SCC is higher in blacks than whites in CC-NSCLC patients(45.0% vs. 36.1%), which is consistent with literature as previous studies have reported that higher incidence of SCC was observed among Black males and females in comparison to white people 15 . Lung squamous cancer is more common in patients with a longer latency, regional stage and history of cervical squamous cell carcinoma.…”
Section: Discussionsupporting
confidence: 91%
“…As regards the impact of cervical cancer patients clinical features on pathological types of lung cancer, our study highlight that the incidence of SCC is higher in blacks than whites in CC-NSCLC patients(45.0% vs. 36.1%), which is consistent with literature as previous studies have reported that higher incidence of SCC was observed among Black males and females in comparison to white people 15 . Lung squamous cancer is more common in patients with a longer latency, regional stage and history of cervical squamous cell carcinoma.…”
Section: Discussionsupporting
confidence: 91%
“…As regards the impact of cervical cancer patients clinical features on pathological types of lung cancer, our study highlight that the incidence of squamous cell carcinoma is higher in blacks than whites in CC-NSCLC patients 45.0% vs. 36.3%), which is consistent with literature as previous studies have reported that higher incidence of squamous cell carcinoma was observed among Black males and females in comparison to white people 15 . Lung squamous cancer is more common in patients with a longer latency, regional stage and history of cervical squamous cell carcinoma.…”
Section: 07%supporting
confidence: 91%
“…Some studies have described that historically, the first wave of increase in adenocarcinoma is partially influenced by the introduction of novel diagnostic methods that can improve access to the lung periphery, where adenocarcinoma predominantly develops. The second wave of increase was related to changes in cigarette composition and design [20,21].…”
Section: Discussionmentioning
confidence: 99%